Treatment of real textile effluent containing indigo blue dye by hybrid system combining adsorption and membrane processes - Ben Salah, Sarra; Missaoui, Mahzoura; Attia, Afef; Lesage, Geoffroy; Heran, Marc; Ben Amar, Raja (Frontiers in Membrane Science and Technology, 2024)
The rapid expansion of the textile industry in Tunisia has resulted in ever-increasing discharges of wastewater, making it necessary to set up treatment systems allowing (i) its discharge into the environment or (ii) to recycle the water in the textile plant. In this study, several unitary operations were tested in order to improve the treated water quality. Thus, the following unit operations were applied: adsorption using Natural Clay (NC) and Powder Activated Carbon (PAC), ultrafiltration (UF) and nanofiltration (NF) individually or in synergy: UF, NF, PAC-UF, NC-UF, UF-NF et Adsorption-UF/NF. The experiments were carried out on real textile effluent containing Indigo blue dye. A threshold concentration was observed above which performance no longer increases. NF alone showed better reduction of COD (67%), color (78%), and turbidity (98%) than UF alone (26%, 48%, 95%, respectively). The coupling UF-NF showed a clear improvement in water quality in terms of color (99%) and COD (98%) with an improvement in the NF flux from 67.81 L/h.m 2 to 90.62 L/h.m 2 . No fouling was observed for NF while it is significant during UF. The used of adsorption as pretreatment to filtration leads to an enhancement of the treatment performances with a removal of 99.9%, 99.5% and 79.5% respectively for turbidity, color and COD for NC-UF and a removal of 100%, 99.4% and 79.6% respectively for turbidity, color and COD for PAC-UF. Moreover, the addition of adsorbent controls the fouling and a constant and high flux is quickly attained and remains stable over time. The use of natural clay as adsorbent represents an economically profitable solution since it can be obtained locally and the clay used can be reused in the ceramic industry as an additive for road surfacing without the need for regeneration.